Anti-Inflammatory Potential of Takokak (Solanum Torvum) Ethanol Extract in Rats Exposed to 7,12-Dimethylbenz[A]Anthracene (Dmba) - Nur Rahman; Sri Anna Marliyati; Muhammad Rizal Martua Damanik; Faisal Anwar (Journal of Biomedicine and Translational Research, 2015)
Background: Takokak fruit (Solanum torvum) is a type of eggplant containing solasodin, solamargin, solasonin and other phytochemicals components with anti-inflammatory and anti-cancer properties. The purpose of this study was to examine the effects of takokak ethanol extract on TNF-α, IL6, and SOD levels.Methods: Experimental factorial study design, with the effect of takokak extract concentration factor (0, 400 and 800 mg/kgBW), takokak extract administration time factor including preventive (weeks 1-7) and curative (weeks 6-12) administration, and necropsy factor (necropsy in weeks 12 and 16). The data obtained included rats body weight, TNF-α, IL-6 and SOD levels.Results: The result showed that the interaction between takokak concentration and handling has significant effect on the increase of TNF-α levels (p=0.003) and the decrease of IL-6 levels (p=0.000). Interaction between takokak concentration, handling and necropsy has significant effect on the increase of SOD levels (p=0.010).Conclusion: Takokak ethanol extract has significant effect on the increase of TNF-α, and SOD levels, and the decrease of IL-6 levels.